AKURASI PREDIKSI HARGA SAHAM ANTM MENGGUNAKAN METODE REGRESI LINIER GANDA VERSUS ARIMA - Sarwo Edy Handoyo; Thea Herawati; Anton Hindardjo (STAI Asy-Syukriyyah, 2014)
The magnitude of the stock price becomes the basis for decision making for investors and company management. Prediction of stock prices become a necessity for them. This study aims to predict the stock price of ANTM and knowing which approach is better for predicting stock prices ANTM between multiple linear regression method with ARIMA method. The results show the method of multiple linear regression and ARIMA significantly ANTM able to predict stock prices that do not vary with the actual average price of shares of ANTM. Multiple linear regression method is able to predict the stock price with a lower mean difference than the actual average price of shares of ANTM. Methods ARIMA models AR(1), able to predict the stock price range lower limit and upper limit that is lower than the actual average price of shares of ANTM.